Experimental Assessment of The 100 mV Polarization Shift Criterion for Cathodic Protection Systems of the Prestressed Concrete Cylinder pipes - Kuwairi, Belied; Elfergani, Hisham (Libyan Journal for Engineering Research, 2017)
In this work, an experimental study was carried out to evaluate the 100 mV polarization shift criterion for confirming the effectiveness of applied cathodic protection viz via zinc sacrificial anodes to arrest progress of corrosion in uncorroded or partially corroded high tensile grade prestressing steel wires of the same grade as the one used to manufacture the prestressed concrete cylinder pipes (PCCP). Total number of 14 wire samples were placed under constant tension approximately 55% of their ultimate tensile strength by the use of specially designed and fabricated holding metal frames. All samples were individually immersed in glass vessels filled with alkaline solutions of pH around 12 and variable chloride ions concentration ranging from 500 to 3000 ppm. With the exception of one wire sample left unprotected; the remaining samples were cathodically protectedby systems of zinc sacrificial anodes such that an average measured polarization shift near 100 mV with variable chloride content in solution was maintained for 9 samples and near 75, 50, and 25 mV with constant chloride content of 3000 ppm. Evaluation of mechanical properties of wire samples suggested that 100 mV criterionand more than sufficient to confirm the adequacy and effectiveness of zinc sacrificial anodes cathodic protection system to arrest progress of corrosion of partially corroded and uncorroded prestressing steel wires in alkaline passivating environment contaminated with chloride ions up to 3000 ppm in solution and for shifts in polarization as low as 25 mV. It was also evident that corrosion progress in the prestressing steel wires can not be arrested in the 3000 ppm chloride environment without the application of cathodic protection.